POTENSI EKOLOGI MANGROVE TINGKAT POHON DAN PANCANG PULAU KABAENA KABUPATEN BOMBANA SULAWESI TENGGARA - Zulkarnain Zulkarnain; Sahindomi Bana; Lies Indriyani (Jurnal Ecogreen, 2018)
ABSTRACTThis study aims to determine the composition and vegetation structure of mangrove forest in Kabena Island, Bombana Regency, especially at the level of trees and sapling which is the focus in the estimation of surface carbon stocks in mangrove forests. Data were collected using a combination method of plots and lines, which were placed intentionally and perpendicular to the shoreline. The measurement data are then analyzed to obtain information on the density, frequency, dominance, the Importance Value Index (IVI) and the diversity index. The results showed that vegetation composition at tree and sapling level was made up of 15 species, which belong to 7 families. The family of Rhizophoraceae and Avicenaceae are the families with the highest number of species. Rhizophora mucronata and Rhizophora apiculata are the most numerous species with very large stem diameters found in the Study Site. The level of diversity at the study site was included in the moderate category with Shannon Wiener's diversity index value at the tree level of 2.29 and the sapling level of 2.28. These results provide an indication that the resilience of mangrove forest ecosystems at the level of trees and tinang on Kabaena Island is moderate.Keywords : Mangrove, Structure, Composition, Diversity, Kabaena Island.